Abortion in Captive Gray Brocket Deer (Mazama gouazoubira) Associated with Colloid Goiter, Hemonchosis and Necrotizing Rumenitis - Gorza, Leonardo Lima; Oliveira, Ellen Cristina de; Lopes, Carlos Eduardo Bastos; da Silva, Eduardo Lazaro de Faria; Hiura, Emy; Flecher, Mayra Cunha; Souza, Tayse Domingues de; Braga, Fábio Ribeiro (Acta Scientiae Veterinariae, 2021)
Background: The gray brocket deer (Mazama gouazoubira) is a specie that shows great adaptability in different habitats and it is the most abundant deer specie in South America. The present work describes for the first time a case of abortion followed by death associated with colloid goiter, massive hemonchosis and necrotizing rumenitis in a captive female gray brocket deer. Case: A 4-year-old female gray brocket deer (M. gouazoubira) raised in captivity had a history of abortion during the last third of gestation. The animal was kept in an enclosure together with 3 other gray brockets deers, being 1 male of the same age and 2 juvenile brocket deer of approximately 1 and 2 years old. The animals were fed with concentrated used as cattle feed and dewormed annually with 1% Ivermectin. The animals' enclosure had vegetation cover formed by grasses and soil. The animals appeared healthy with no behavioral changes. The day after the stillbirth, the mother was found dead in the enclosure and sent to the animal pathology sector of the University of Vila Velha (UVV), Brazil. Necropsy revealed that thyroid lobules were highly increased in volume and histopathological findings were compatible with colloid goiter. A large number of nematodes were found in the abomasal content,totalizing 11,626 helminths, which were morphologically characterized as Haemonchus contortus. Grossly, the serous and ruminal mucosa exhibited an extensively reddish focal area with irregular contour, surface ulceration and a firm consistency. Microscopically, a severe necrotizing rumenitis was diagnosed. The liver showed pale multifocal areas on the subcapsular surface,friable to the touch which deepened when cut. Histopathological analysis revealed an accentuated multifocal panlobular coagulative necrosis, characterizing an acute liver necrosis. Discussion: Iodine is a mineral of great importance for thyroid hormones synthesis and your requirements are higher during pregnancy and lactation. Diets deficient in iodine causes a reduction in the basal activity of the hormones triiodothyronine (T3) and thyroxine (T4) and over-stimulation of the thyroid by thyroid stimulating hormone (TSH), resulting in goiter. In the present case, it is possible that the shortage of iodine in diet caused a goiter and, as a consequence, triggered the abortion. Haemonchus contortus is a pathogenic nematode of small ruminants, leading to decreased productivity and death in some cases as a result of anemia and hypoxia. The contact between domestic and wild animals, resulting in the emergence of infectious diseases and the spread of pathogens among species. In the present case, manual counting accounted for 11,626 H. contortus larvae, characterizing a massive infection and justifying the condition of severe anemia. The high parasitic load shown in this case points out this parasite's importance related to this species in captivity. In general, inflammatory lesions in the rumen are results of excessive intake of fermentable carbohydrates, which leads to a considerable decrease in ruminal pH and leads to a high proliferation of lactic acid bacteria. This lesion has been previously reported in cervids. This case of comorbidities demonstrates that failures in nutritional and health handling, may cause simultaneous multiple diseases leading to death. Preventive measures for helminth parasite control and a proper feeding management with an adequate diet must be provided in order to preserve the species in captivity. Keywords: colloid goiter, abortion, cervids, Haemonchus contortus.